The Influence of the Tharuhat Autonomous State Council (Tasc) In Kailali District in The Far-Western Tarai - Maycock, Matthew (New Angle: Nepal Journal of Social Science and Public Policy, 2011)
The signing of the Comprehensive Peace Accord in 2006 and Nepal entering a post-conflict era have been associated with the emergence of various organisations and movements often formed along ethnic lines. The Tharuhat Autonomous State Council (TASC) is one such movement that is the focus of this paper but more generally has received relatively limited focus within academia. Within the context of Kailali district in far-west Nepal, this paper explores various characteristics and policies of the wider Tharuhat movement focusing on the vision for an autonomous Tharu state. It will highlight some of the successes and problems that the movement faces. Furthermore, this paper will explore a number of tensions between the national Tharuhat discourse and how this finds meaning and resonance at the local level where activists are attempting to engage with the Tharu community. Ultimately this paper examines the extent to which the Tharuhat movement represents a new more political stage in the wider Tharu ethnic movement.